THE POWER OF DIGITAL INFLUENCE: HOW SOCIAL MEDIA DRIVES BRAND AWARENESS AND PURCHASE INTENTIONS AMONG GEN Z - Sherliana Lim; Keni Keni (DeReMa (Development Research of Management): Jurnal Manajemen)
This study explores the impact of influencer credibility, user-generated content (UGC), and celebrity endorsement on purchase intention among Generation Z in Jabodetabek, with brand awareness as a mediating variable. This study collected data from 186 respondents who were skincare products users and the data were analyzed by using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that UGC and brand awareness significantly and positively influence purchase intention. However, influencer credibility and celebrity endorsement do not affect purchase intention significantly. Furthermore, brand awareness does not mediate the impact of influencer credibility and celebrity endorsement on purchase intention. These findings highlight the importance of prioritizing user-generated content and brand awareness in shaping consumer’s purchase intention. Moreover, for skincare companies, focusing on authentic user interactions and fostering brand familiarity can enhance marketing strategies, particularly in competitive digital environments. Furthermore, this study offers insights regarding how digital marketing elements influence consumer’s behavior and provides feasible recommendations for businesses who target young and media-savvy customers. The results underline the evolving role of digital content and branding in driving purchase intentions, suggesting that companies should adapt their strategies to align with the expectations of Generation Z, who value relatability and authenticity.